The role of ostrich in shaping the landscape use patterns of humans and hyenas on the southern coast of South Africa during the late Pleistocene - Hodgkins, J; le Roux, P; Marean, CW; Penkman, K; Crisp, M; Fisher, E; Lee-Thorp, J (Routledge, 2018)
How have prey species structured the way modern humans (Homo sapiens) and other social carnivores utilize the landscape? The availability, location, diversity, and abundance of food resources play a critical role in influencing hunter-gatherer and carnivore mobility (Kelly, 1983). Thus, the behavioral patterns of other living organisms are powerful forces in shaping human behavior. In this chapter, we will explore the role that ostrich play in shaping subsistence patterns in early modern humans and brown hyena (Parahyaena brunnea) at two sites located in the Pinnacle Point (PP) cave and rock shelter complex in South Africa: PP5-6 and PP30. This project tracking multispecies behavioral ties is aided by a bioavailable 87Sr/86Sr isoscape map created for the region surrounding Pinnacle Point. The map was generated by determining the 87Sr/86Sr values found in bedrock along the South African coast, coastal forelands, and into the inland mountain chains. Ostrich breed within defended territories, consuming plant food within those territories, and thus their tissues acquire 87Sr/86Sr values from a restricted area. The 87Sr/86Sr values obtained from ostrich eggshell fragments deposited at PP5-6 and PP30 should therefore provide information about where on the landscape human hunter-gatherers and social carnivores encountered and collected eggs.